Oxidative stress-CBP axis modulates MOB1 acetylation and activates the Hippo signaling pathway. Issue 7 (29th March 2022) - Jin, Jiaqi; Zhang, Lei; Li, Xueying; Xu, Weizhi; Yang, Siyuan; Song, Jiagui; Zhang, Wenhao; Zhan, Jun; Luo, Jianyuan; Zhang, Hongquan
Abstract: Reactive oxygen species (ROS) are constantly produced in cells, an excess of which causes oxidative stress. ROS has been linked to regulation of the Hippo pathway; however, the underlying detailed mechanisms remain unclear. Here, we report that MOB1, a substrate of MST1/2 and co-activator of LATS1/2 in the canonical Hippo pathway, interacts with and is acetylated at lysine 11 by acetyltransferase CBP and deacetylated by HDAC6. MOB1-K11 acetylation stabilizes itself by reducing its binding capacity with E3 ligase Praja2 and subsequent ubiquitination. MOB1-K11 acetylation increases its phosphorylation and activates LATS1. Importantly, upstream oxidative stress signals promote MOB1 acetylation by suppressing CBP degradation, independent of MST1/2 kinase activity and HDAC6 deacetylation effect, thereby linking oxidative stress to activation of the Hippo pathway. Functionally, the acetylation-deficient mutant MOB1-K11R promotes lung cancer cell proliferation, migration and invasion in vitro and accelerates tumor growth in vivo, compared to the wild-type MOB1. Clinically, acetylated MOB1 corresponds to better prediction of overall survival in patients with non-small cell lung cancer. Therefore, as demonstrated, an oxidative stress-CBP regulatory axis controls MOB1-K11 acetylation and activates LATS1, thereby activating the Hippo pathway and suppressing YAP/TAZ nuclear translocation and tumor progression.